A Concurrent Dual-Beam Phased-Array Doppler Radar Using MIMO Beamforming Techniques for Short-Range Vital-Signs Monitoring - Nosrati, Mehrdad; Shahsavari, Shahram; Lee, Sanghoon; Wang, Hua; Tavassolian, Negar (IEEE transactions on antennas and propagation, 2019)
This paper presents the theoretical and experimental results of a new approach for multitarget vital-signs monitoring using an electromagnetic-based Doppler radar. A phased-array radar is designed and implemented using a hybrid beamforming architecture to generate two simultaneous beams. The proposed system significantly mitigates the phase collision problem in the presence of multiple targets. Comprehensive discussions on the theory of multibeam systems alongside detailed simulations are provided. For the purpose of demonstration, a prototype dual-beam phased-array continuous-wave Doppler radar has been designed and implemented at 2.4 GHz. The system is fully characterized, and the measurement results confirm the feasibility of the proposed method. The experimental measurements show that for the first time, the breathing rates of two individuals can be monitored at the same time and using the same frequency. Several practical aspects of the system are examined, and a pilot study on the subject tracking is presented. The proposed dual-beam system prevents the phase collision of the signatures of the targets and hence provides multiperson detection capability to the system.